High photovoltaic performance of inkjet printed polymer: fullerene blends - Choulis, Stelios A.; Hoth, Claudia N.; Schilinsky, Pavel (My University, 2007)
The performance of highly efficient inkjet printed organic bulk heterojunction solar cells was analyzed and the morphologies and interfacial properties of the inkjet printed polymer:fullerene blend photoactive layer determined by a suitable solvent formulation were demonstrated. It is observed that a mesitylene concentration less than 32% in the solvent mixture results in poor wetting and spreading of the solution, while concentration higher than 32% result in lower solubility of the materials. The results show that an inkjet platen temperature of 40°C results in a uniform film and reliable printing with respect to the spreading and film formation. The increase in the viscosity at the nozzle orifice affects the characteristics of the inkjet droplets in terms of velocity, volume, and angle deviation
Keywords: Polymers; Fullerenes; Organic solvents; Ink-jet printing; Solar cells; Solubility; Wetting